Antifungal Potential Of The Sponge Styllisa Flabelliformis Against The Pathogenic And Resistant Aspergillus Fungi - Tomasoa, Aprelia Martina; Rieuwpassa, Frets Jonas; Azhari, Deidy; Ijong, Frans Gruber; Mege, Revolson Alexius; Tanod, Wendy Alexander; Balansa, Walter (Jurnal Ilmiah Platax, 2023)
Together with bacterial and viral infection, fungal infection represents the world's top ten killer diseases, desperately requiring new antifungal drugs. This research aimed to evaluate the antifungal activity of the sponge Styllisa flabelliformis against the pathogenic fungi Aspergillus flavus and Aspergillus parasiticus by the standard agar diffusion technique. Three concentrations (1, 10, and 10 mg/mL) for the extract and 0.5 mg/mL for ketoconazole and fluconazole were prepared and evaluated in triplicate against the tested fungi. Whereas ketoconazole poorly inhibited A. parasiticus and fluconazole weakly inhibited A. flavus, the extract of S. flabelliformis exerted antifungal activity against A. parasiticus (6.8 ± 1.8; 8.3 ± 3.2; and 9.5 ± 2.1) mm and A. flavus (6.8 ± 1.1; 11.5 ± 1.4; and 14.3 ± 1.1) mm 1, 10 and 100 mg/mL respectively. PASS analysis showed jasplakinolide as a promising antifungal agent with potential activity (Pa) of 0.736. STITCH analysis further confirmed that jasplakinolide worked by inhibiting the expression of cytoskeleton genes that prevented fungi from synthesizing chitin and inhibiting the formation of the fungi’s cell walls and hyphae, different from the ergosterol synthesis inhibition in ketoconazole and fluconazole, implying the potential of jasplakinolide as an antifungal agent.